Association between intracranial and extracranial atherosclerosis and white matter hyperintensities: a systematic review and meta-analysis - Zhang, Wenyuan; Fu, Fangwang; Zhan, Zhenxiang (Frontiers in Aging Neuroscience, 2024)
Background White matter hyperintensities (WMHs) are key neuroimaging markers of cerebral small vessel diseases. This study aimed to investigate whether intracranial and extracranial atherosclerotic stenosis is associated with WMHs. Methods Following a previously registered protocol (PROSPERO protocol: CRD42023407465), PubMed, Web of Science, and Embase were systematically searched for relevant literature published until March 2023. Cross-sectional studies examining the association between intracranial and extracranial atherosclerotic stenosis and WMHs were included. Random effects models were used to calculate the pooled estimates. Results Twenty-one eligible studies, including 10,841 participants, were identified. Intracranial and extracranial atherosclerotic stenosis was associated with an increased risk of WMHs (OR 1.80, 95% CI 1.25–2.57, I2 = 75%) and increased WMH volumes (SMD 0.40, 95% CI 0.18–0.63, I2 = 63%). Heterogeneity resulted from the WMHs rating method and the location. Extracranial atherosclerotic stenosis (ECAS) was significantly associated with WMHs (OR 2.10, 95% CI 1.22–3.62, I2 = 71%), but intracranial atherosclerotic stenosis (ICAS) was insignificantly associated with WMHs (OR 1.75, 95% CI 0.97–3.15, I2 = 84%). The association was stable in the subgroup analysis based on WMHs location, which included deep WMHs and periventricular WMHs. Conclusion Intracranial and extracranial atherosclerotic stenosis is associated with WMHs. This association is significant in ECAS, but attenuated in ICAS.